Grünberger Hauskalender - Dylewska, Agnieszka (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the first half of the 20th century, book calendars were widespread among all social groups. Thanks to their universality and fulfilment of the functions of both an informational and literary almanac and a classic calendar, they found their use as various types of guides, became a source of entertainment and knowledge, and, thanks to their easy availability and mass distribution, they had an impact on cultural and social consciousness.
Keywords: kalendarz książkowy; Dolny Śląsk; literatura regionalna; literatura trywialna; Zielona Góra; Kożuchów (woj. lubuskie); mikroprowincja; book calendar; Lower Silesia; regional literature; trivial literature; microprovince